Clinical-epidemiological profile of patients with liver cancer treated at a tertiary center: A cross-sectional study (Research, Society and Development, 2025)
Objective: To outline the clinical and epidemiological profile of patients diagnosed with liver cancer treated at a tertiary health center. Methods: This is a cross-sectional study, which collected, in a non-probabilistic way, data from the medical records of patients treated at the Hospital de Clínicas, Passo Fundo - RS, between January 2011 and December 2020. The findings were categorized into data from identification and sociodemographic data, health characteristics, hospital case outcome and liver cancer outcome. Results: Of the 117 patients, 65% were men. A total of 91% were white, aged 68 ± 14 years. Of the liver tumors, 40% corresponded to liver metastases, while among the primary neoplasms, hepatocellular carcinoma was responsible for 86% of the diagnoses. Of the diagnoses of hepatocellular carcinoma, there was a predominance of males, with 80% of cases aged 71 ± 9.5 years. Of the risk factors associated with neoplasia, alcoholic cirrhosis was the most prevalent (52%), being mainly related to males. Conclusion: Liver cancer is more prevalent in men with a mean age of 68 years. Of the liver cancers, hepatocellular carcinoma has the highest prevalence, with a clinical profile well outlined in the literature, affecting mainly men over 70 years of age with liver cirrhosis associated with excessive alcohol intake and infection with hepatitis C and B viruses. Part of the etiological components and risk factors for hepatocellular carcinoma are preventable and avoidable.